Contemporary Logistics in China : Reformation and Perpetuation - Jiao, Zhi-lun; Lee, Shao-ju; Wang, Ling (Of Nan kai da xue (Tianjin, China)); Liu, Binglian (Springer, 2017)
This book is the seventh volume in a series entitled "Contemporary Logistics in China," authored by researchers from the Logistics Center at Nankai University. In the spirit of the six preceding annual volumes, this book carries on the ideal of providing a systematic exposition on the logistics development in China for the English-speaking community at large. Specially, this volume captures China's logistics development at a crucial turning point. On the one hand, it reflects the new horizon advocated by the Government's One-Belt-One-Road Initiative global cooperation strategy; on the other, it explores the Internet revolution, which has had major impacts on e-commerce and urban logistics in China. Subjects covered in this volume encompass the macro-factors pertaining to logistics development, region-specific plans, industry-wide transformation, globally-oriented moves, and current hot topics. The expositions on and analyses of these subjects are based on the latest available sources and statistical data. As with the previous volumes, the ultimate aim of this book is to present a timely portrait of the rapid growth of China's logistics market and the status quo of its logistics industry. In so doing, the book offers an in-depth analysis of critical issues involved in the ongoing dynamic and multi-faceted development, and provides a valuable reference resource for interested readers in the academic and professional fields.
Keywords: Business logistics -- China.; Operations research -- China.; Decision making -- China.; Industrial organization -- China.; China.; elektronické knihy; electronic books